Enhanced mechanical strength of polypropylene bionanocomposites through spray-dried nanocrystalline cellulose reinforcement - Sabaruddin, Fatimah Athiyah; Ariffin, Hidayah; Shazleen, Siti Shazra; Ng Yee Foong, Lawrence; Rujitanaroj, Pim-on; Thitiwutthisakul, Kasinee; Permpaisarnsakul, Patcharin; Tinnasulanon, Phungjai (Royal Society of Chemistry, 2025)
The polymer industry is increasingly focusing on nanocellulose-based polymer composites owing to their remarkable mechanical properties. However, achieving well-dispersed nanocellulose fillers remains challenging. This unique study compares one-step and two-step melt-blending processes for incorporating spray-dried nanocrystalline cellulose (SD-NCC) at 3 and 5 wt% into polypropylene with a 3 wt% MAPP coupling agent. Both the one-step and two-step compounding processes were evaluated for their effects on nanocellulose distribution and mechanical performance. One-step PP/SD-NCC3 achieved the best properties: 34.8 MPa tensile, 57.3 MPa flexural, and 2.08 kJ m−2 impact strengths. SEM-EDX confirmed good SD-NCC distribution. Two-step 5 wt% SD-NCC showed slight improvements in mechanical, crystallinity, and thermal properties because of its better dispersion, but the one-step process was sufficient for achieving excellent performance. These findings suggest that spray-dried NCC can streamline compounding for large-scale applications. © 2024 The Author(s).